Victimization, offending, and perceived risk for early violent death - Skubak Tillyer, Marie (Criminal justice and behavior, 2015)
Research indicates that adolescents tend to overestimate their risk for early death, and those who anticipate early deaths are at risk for numerous negative consequences. Little is known, however, about the factors that influence early violent death expectations. The present study develops and tests hypotheses about the influence of victimization and offending on perceived risk for early violent death using longitudinal data collected from a nationally representative sample of American adolescents. Logistic regression analysis was used to estimate the effects of prior violent victimization, witnessing serious violence, and various types of delinquency on adolescents? perceptions that there is a 50% or greater chance they will be killed by the age of 21. Implications for theory, policy, and future research are discussed.